Analisis Buku Biologi SMA Kelas X Materi Kingdom Animalia Berdasarkan Literasi Sains Se-Kabupaten Deli Serdang - Fitriana Siregar; Hasruddin Hasruddin; Ely Djulia (Jurnal Pendidikan Biologi, 2016)
The aimed of this research was to know level of scientific literacy of Animalia Kingdom on senior high school biology book at grade X in Deliserdang. The method of this research was descriptive quantitative by analyzing 7 the Biology Books from different publisher for grade X on animalia Kingdom topic. Books was assessed by researcher. Researcher assessed Animalia Kingdom on Senior High School biology books at grade X in Deliserdang based of scale questioner Animalia Kingdom on Senior High School biology books grade X with science of the body of knowladge, science as a way of investigating, science as a way of thinking, and interaction science, technology, and society. Result of this research shown that  persentage of thema science as a body of knowledge was 21,86%, persentage of science as a way of investigating was 15,27%, persentage of science as a way of thinking was 11,91%, and persentage of interaction science, technology, and society was 10,36%. It can be concluded that percentage of scientific literacy of Animalia Kingdom on Senior High School biology books at grade X in Deliserdang was 59,42% (not yet scientific literacy).